Engineered Mg-modified biochar-based sorbent for arsenic separation and pre-concentration - Vladimír Frišták; Kristína Beliančínová; Lucia Polťáková; Eduardo Moreno-Jimenéz; Andrew R. Zimmerman; Libor Ďuriška; Ivona Černičková; Haywood Dail Laughinghouse IV; Martin Pipíška (Scientific Reports, 2024)
Abstract The utilization of biochar as a relatively efficient sorbent or stationary phase for the separation and preconcentration of a wide range of analytes represents an innovative approach in current sample pretreatment methods. Appropriate pre- and post-pyrolysis modification of the input precursor and pyrolysis product, respectively, allows targeted design of the physicochemical properties and sorption characteristics of the resulting sorbent. The present work deals with the preparation of pyrolysis materials based on unmodified cattail leaf biomass (BC) and its Mg-modified analogue (MgBC) by a slow pyrolysis process at 500 °C and a residence time of 1 h in a pyrolysis reactor. Physicochemical characterization of BC and MgBC carried out by pH, total C, N, surface size analysis (SSA), 13C NMR, SEM-EDX and XRD confirmed significant morphological and mineralogical differences between the prepared sorbents. By performing sorption experiments using a model anionic analyte (As) and application of Langmuir isotherm, we found that the predicted maximum sorption capacity of MgBC for As is 13.5-fold higher than that of BC. The sorption process of As by both sorbents is best described by the Sips adsorption isotherm (R2 ≥ 0.995) and a pseudo-nth order kinetic model (R2 ≥ 0.997). The optimum pH for As sorption by BC and MgBC sorbents is in the interval 5–6. The presence of competitive phosphate anions (equimolar concentration of 1:1) in the solution significantly reduces the sorption capacity of MgBC for As by 40% for BC by 70%. The presence of Cl- ions showed no significant effect on the sorption capacity of Bc and MgBC for As. Both sorbents were best recovered using 0.1 mol/L NaOH solution when the desorption efficiency for both sorbents was more than 95%. The MgBC sorbent showed 35% retention of As from the real sample in the model SPE column at a flow rate of 0.12 mL/s. Based on the obtained knowledge, it is evident that biochar-based sorbent prepared from Mg-modified precursor represents an effective sorbent for anionic forms of analytes and opens the possibility of its use also in preconcentration and separation techniques.